Self-publishing trade books in South Africa: opportunities, challenges, and implications - Nyamapfene, Lorraine (University of the Witwatersrand, Johannesburg, 2025)
This study explores the self-publishing landscape in South Africa, focusing on author motivations, experiences, and implications for key stakeholders, including authors, traditional publishers, booksellers, publishing service providers, and readers. Employing qualitative methods, such as questionnaires, interviews, focus groups, and document analysis, the research addresses a gap in empirical evidence about self-publishing within the South African trade sector. Findings reveal that authors are driven to self-publish for interconnected reasons, including rejection by traditional publishers, potential financial benefits, a desire for creative control, and publishing prestige. The satisfactions authors derive align closely with these motivations, with creative control emerging as a paramount benefit. Authors highly value their autonomy over copyright, production, distribution, and profits, making many reluctant to pursue traditional publishing. While financial rewards represent another significant advantage, substantial monetary success remains limited to a select few. The quality of self- published books varies widely, with most failing to meet professional standards, although some match the quality of traditionally published books. Authors face persistent challenges, including stigma and distribution barriers, yet self-publishing remains a vital alternative in South Africa’s constrained traditional publishing market. The study highlights how self- publishing amplifies diverse voices and genres, with publishing service providers playing a crucial role in maintaining quality standards. However, the reach of self-published works is often limited by barriers within the traditional publishing landscape. These findings offer practical insights for authors, publishers, and service providers navigating the evolving self- publishing ecosystem, underscoring its potential to democratize publishing while highlighting areas for improvement.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Publishing, in the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; self-publishing; gatekeeping; author motivations; creative control; literary diversity; stigma; discoverability; South Africa; SDG-4: Quality education; SDG-8: Decent work and economic growth